The effects of trichloroacetic acid in the treatment of post-acne atrophic scars - Prodanović, Anastasija; Milanovic, Isidora M (Education and Research in Health Sciences, 2022)
IntroductionThe atrophic-scars treatment, lasts for several months. The therapy should prevent or reduce scarring. It`s pathogenesis are result of sebum hyperproduction, follicular epidermal hyperkeratinization, the activity of Propionibacterium acnes, immune response. The TCA piling stimulates tissue regeneration  causing protein deposition, coagulation necrosis, exfoliation of photo-damaged cells. The goalDemonstrate the effects of TCA peels on atrophic-scars and the significance of skin-care after it’s.  MethodologyThe prepared skin is TCA solution treated, in circular motions, in five-steps. The eyes are covered and protected. The next layers were applied in 3 steps. Case study: subject, skin phototype 3, with postacnotic atrophic-scars. The therapy: the treatment of TCA - 50% to atrophic regions looking after frosting (coagulation of epidermal and dermal proteins) under the physician supervision. Results and DiscussionThe first treatment decreased the number of active acne lesions and inflammation, atrophic-scars are less visible. The skin is smooth and gentle. There is no postinflammatory hyperpigmentation. The Chemical peels are simple to performe at the histological level we need, have a low complication rate, low costs. Skin-care after it`s are simple cleansing. Hydra-Soothing fluid, a non-greasy moisturizing milk, repairs and nourishes skin. Sun protection is mandatory. ConclusionTCA is stable, inexpensive, does not cause systemic toxicity. Peeling is easy to perform, the depth of peeling correlates with the intensity of frosting. There is no need to neutralize TCA. If performed correctly, TCA peels achieve histological and clinical improvement of the skin. Key words: acne-atrophic scars, TCA peeling, skin-care after chemical peeling
Keywords: acne-atrophic scars; TCA peeling; skin-care after chemical peeling